Pengaruh Pengetahuan, Kompetensi, Dan Integritas Auditorterhadap Kualitas Audit (Studi Kasus Pada Kantor Akuntan Publik Di Surabaya) - Fadia Insyira; Sri Trisnaningsih (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The purpose of this study is to examine how the influence of knowledge, competence, and integrity of auditors on the quality of audits conducted by Public Accounting Firms in Surabaya. This research is quantitative. This study involved auditors from a Public Accounting Firm in Surabaya. A total of 54 auditors became research respondents. The data source is primary data by distributing questionnaires directly. In this study, probability sampling was used in the sampling technique. Multiple linear regression analysis became the analytical technique used with the help of the SPSS 25 program. The results showed, a) knowledge showed sig. of 0.004 which means <0.05; b) competence shows sig. of 0.000 which means <0.05; c) integrity shows sig. of 0.398 which means > 0.05. In conclusion, knowledge and competence have a positive and significant effect on audit quality, while integrity has a negative and insignificant effect on audit quality. Keywords: Integrity, Audit Quality, Competence, Knowledge